A model for improving and assessing outpatient stewardship initiatives for acute respiratory infection. (26th July 2019) - Guzik, Joan; Kothari, Pooja; Sharp, Misha; Ostrowsky, Belinda; Patel, Gopi; ,
Abstract : Many hospitals have established inpatient antibiotic stewardship programs (ASPs), but outpatient activities remain limited. In 2016, the United Hospital Fund (UHF), an independent nonprofit working to build a more effective healthcare system for every New Yorker, launched a 2-stage grant-funded initiative to evaluate outpatient antibiotic stewardship, focusing on adults with acute respiratory infections (ARIs). Conclusions from stage 1 included few outpatient antibiotic stewardship activities, variation in prescribing, macrolides as the most commonly prescribed antibiotic, and provider interest in improving prescribing. 1